Evaluation of Time to Positivity of Blood Cultures in Pediatric Patients - Gizem Guner Ozenen; Tansu Aydoğan; Zühal Ümit; Nimet Melis Bilen; Irem Ersayoglu; Pınar Yazıcı Özkaya; Miray Karakoyun; Feriha Cilli; Zumrut Sahbudak Bal (Journal of Global Antimicrobial Resistance)
AIM: We aimed to evaluate the microbiological characteristics of bloodstream infections (BSI) in children and the relationship between the time to positivity (TTP) of blood cultures and mortality. BACKGROUND: The early detection of causative microorganisms for BSI helps clinicians to initiate appropriate antimicrobials to reduce mortality. METHODS: A retrospective study was designed to evaluate the TTP of all the blood cultures from children with suspected BSIs for one year at Ege University. Episodes with no growths or contaminations were excluded from the study. RESULTS: A total of 890 BSI were evaluated and 272 episodes in 170 patients were included in the study. The median age of the patients was 2.3 years (min 2 months - 17.5 years) and 60.7% (n=165) were male. The most common underlying disease was solid-hematological malignancy (25%, n=68); followed by solid organ-bone marrow transplantation (19.9%, n=54) and intestinal failure (19.5%, n=53). The isolated microorganisms were gram-positive bacteria in 51.8% (n=141) episodes, gram-negative bacteria in 30.5% (n=83), multiple growths in 9.6% (n=26), and fungi in 8.1% (n=22). The median TTP of all positive blood cultures was 16 (min 5.5- max 103.5) hours. The TTP of Gram-negative strains was significantly shorter than that of Gram-positive strains (13.9 vs 17.5 hours, p<0.001) and fungi (13.9 vs 28.6 hours, p<0.001).. Mortality rates did not differ according to TTP (p>0.05). CONCLUSIONS: The TTP in gram-negative agents was found to be shorter than in gram-positive and fungal agents. TTP helps identify the causative microorganisms and initiate appropriate treatment rapidly.